NSTP Online : database quality from the users' perspective. - Heang, Swee L. (Curtin University, 1998)
NSTP Online is a news database produced by The New Straits Times Press (Kuala Lumpur, Malaysia). This service is comprised of two major components - Newsbase and Special Databases, which provide archival Malaysian information. NSTP Online is the trade name of the online database available commercially and internally to the organisation.Quality issues are acknowledged by database producers but are often overlooked due to resource, technology and human constraints. The key quality issues include contents, data quality, customer support and database structure. The objective of investigating these issues from the users' perspective is because it is the major issue from the business point of view. The few database quality studies documented in the literature are limited to methodological development.Quality issues from the users' perspective are difficult to measure due to the intangible nature of information, the researcher's dependence on the subjective opinions of the users and the variables associated with experience and costs. The aim of the study is to investigate the problems affecting the use of information and identify areas requiring further examination by the database producer.The results of this investigation draw upon the writer's experience with NSTP Online and the feedback obtained from the questionnaire and interviews conducted in Malaysia. This paper examines the differences in usage, training, support and data retrieval among the external and internal users. Despite the fact that NSTP Online needs to be improved in terms of contents, currency, technology and telecommunication, the service is still regarded as an useful information tool by the users.The paper highlights the many problems that require further planning and improvement for internal and external users. These include developing an appropriate channel of communication, an improved understanding of the requirements and expectations of the users, and an increased depth to the contents available to the customers. It is recommended that future improvement be focused on the problems faced by the users and the way in which a number of these can be overcome with the use of more advanced technology.